MANAGEMENT RESOURCE-ECOLOGICAL SAFETY AT REGIONAL LEVEL - Самойлік, М. С. (Scientific Progress & Innovations, 2014)
In the articles worked out SWOT-analysis of factors of existent control functioning system by resource-ecological safety (RES) and a regional to the cluster case of RES frame is formed, that can be realized for two cases: opening of innovative-investment potential of secondary material and power resources; creation of productive clusters ecological that is determined by the productive specific of regions. Conceptual principles of cluster politics of management of resource-ecological safety are worked out in a region, the algorithm of realization of that includes: preparatory, analytical, organizationally-economic the stages and efficiency estimation of cluster activity that envisages development of scenario of long-term development of cluster also, including prognoses of functioning on separate directions, forming of estimation methodology of cluster efficiency from the point of effects sinergistical view and contribution to strategy of region development in relation to providing RES.